Healthy lifestyle index and risk of gastric adenocarcinoma in the EPIC cohort study. Issue 3 (13th February 2015) - Buckland, G.; Travier, N.; Huerta, J.M.; Bueno‐de‐Mesquita, H.B(as); Siersema, P.D.; Skeie, G.; Weiderpass, E.; Engeset, D.; Ericson, U.; Ohlsson, B.; Agudo, A.; Romieu, I.; et al.
<x xml:space="preserve">Abstract</x> Several modifiable lifestyle factors, including smoking, alcohol, certain dietary factors and weight are independently associated with gastric cancer (GC); however, their combined impact on GC risk is unknown. We constructed a healthy lifestyle index to investigate the joint influence of these behaviors on GC risk within the European Prospective Investigation into Cancer and Nutrition (EPIC) cohort. The analysis included 461, 550 participants (662 first incident GC cases) with a mean follow‐up of 11.4 years. A healthy lifestyle index was constructed, assigning 1 point for each healthy behavior related to smoking status, alcohol consumption and diet quality (represented by the Mediterranean diet) for assessing overall GC and also body mass index for cardia GC and 0 points otherwise. Risk of GC was calculated using Cox proportional hazards regression models while adjusting for relevant confounders. The highest versus lowest score in the healthy lifestyle index was associated with a significant lower risk of GC, by 51% overall (HR 0.49 95% CI 0.35, 0.70), by 77% for cardia GC (HR 0.23 95% CI 0.08, 0.68) and by 47% for noncardia GC (HR 0.53 (95% CI 0.32, 0.87), p‐trends<0.001. Population attributable risk calculations showed that 18.8% of all GC and 62.4% of cardia GC cases could have been prevented if participants in this population had followed the healthy lifestyle behaviors of this index. Adopting several healthy lifestyle behaviors including not smoking, limiting alcohol consumption, eating a healthy diet and maintaining a normal weight is associated with a large decreased risk of GC.